Investigation of Pendulum Structures for Rotational Energy Harvesting from Human Motion. (November 2015) - Ylli, K; Hoffmann, D; Willmann, A; Folkmer, B; Manoli, Y
Abstract: Energy Harvesting from human motion as a means of powering body-worn devices has been in the focus of research groups for several years now. This work presents a rotational inductive energy harvester that can generate a sufficient amount of energy during normal walking to power small electronic systems. Three pendulum structures and their geometrical parameters are investigated in detail through a system model and system simulations. Based on these results a prototype device is fabricated. The masses and angles between pendulum arms can be changed for the experiments. The device is tested under real-world conditions and generates an average power of up to 23.39 mW across a resistance equal to the coil resistance of the optimal pendulum configuration. A regulated power output of the total system including power management of 3.3 mW is achieved.